O Intercâmbio comercial Brasil-Índia: uma análise de 2003 a 2018 - Rabelo, Ingrid de Sales (2019)
The present work aims to analyse the commercial flow between Brazil and India from 2003 to 2018, identifying the main exported and imported products and characterizing the nature of this trade. For this purpose, two indexes were used: normalized revealed comparative advantage index to identify Brazilian products with competitive advantage and the Grubel-Lloyd index to measure the degree of intra-industrial commercial activity. The results show that, according to the normalized revealed comparative advantage index, Brazil has comparative advantage in low technological intensity sectors. Furthermore, the commercial exchange between the two countries expresses an inter-industrial pattern during the analyzed period. The research indicates that Brazil-India trade did not contribute to Brazilian external vulnerability, due to the significant participation of commodities in the list of exports.